‘HDCSW 18’ wheat the first ever variety for conservation agriculture in India - Yadav, Rajbir; Gaikwad, Kiran; Kumar, Manjeet; Kumar, Naresh (Indian Farming, 2018)
The ‘HDCSW 18’ wheat showed higher yield potential and suitable rice-wheat cropping system in Delhi and NCR. Terminal heat has caused great fluctuation in wheat production over the years (beween 2012-13 and 2015-16) and seeding of wheat early through varieties like ‘HDCSW 18’ wheat will provide the scope from escaping the terminal heat and getting assured yield.